Effects of crystallographic orientation on the superelastic response of FeMnAlNi single crystals. (15th April 2016) - Tseng, L.W.; Ma, Ji; Wang, S.J.; Karaman, I.; Chumlyakov, Y.I.
Abstract: The effects of crystal orientation on the tensile superelastic response of the Fe43.5 Mn34 Al15 Ni7.5 single crystalline shape memory alloy, oriented along the < 100 > and < 123 > directions were investigated. The single crystals aged at 200 °C for 3 h demonstrated superelastic strains of 3.6% along the < 100 > orientation and 7.8% along the < 123 > orientation. Although the theoretical transformation strain in the < 100 > orientation is higher than that in the < 123 > orientation, the < 123 > oriented single crystals demonstrate better superelastic recovery in tension due to a higher number of active martensite variants, which promote better accommodation of internal strains and help minimize defect formation during transformation. Graphical abstract: Recently discovered FeMnNiAl Shape Memory Alloys demonstrate strong crystallographic orientation dependence of superelastic recovery. This is a consequence of the competition between multi-variant martensite formation and massive dislocation activity in accommodating incompatibility between martensite and austenite.